2014
DOI: 10.1039/c4ob00447g
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly of peptides to nanostructures

Abstract: The formation of well-ordered nanostructures through self-assembly of diverse organic and inorganic building blocks has drawn much attention owing to their potential applications in biology and chemistry. Among all organic building blocks, peptides are one of the most promising platforms due to their biocompatibility, chemical diversity, and resemblance with proteins. Inspired from the protein assembly in biological systems, various self-assembled peptide structures have been constructed using several amino ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
194
1
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 259 publications
(200 citation statements)
references
References 90 publications
2
194
1
3
Order By: Relevance
“…12 Ren et al also found that the content of HCNFs strongly depended on the type of catalytic supports and ratio of Cu/support. 12 At present, preparing helical nanofibers, [13][14][15][16] such as HCNFs, using novel catalyst has attracted great interest from researchers in the field of synthesis and related nanomaterials. [17][18][19] However, few works in the literature are concerned with the interaction between the ZnO matrix and Cu nanocrystals in helical fiber synthesis, which may have a great influence on the catalysts' properties.…”
Section: Introductionmentioning
confidence: 99%
“…12 Ren et al also found that the content of HCNFs strongly depended on the type of catalytic supports and ratio of Cu/support. 12 At present, preparing helical nanofibers, [13][14][15][16] such as HCNFs, using novel catalyst has attracted great interest from researchers in the field of synthesis and related nanomaterials. [17][18][19] However, few works in the literature are concerned with the interaction between the ZnO matrix and Cu nanocrystals in helical fiber synthesis, which may have a great influence on the catalysts' properties.…”
Section: Introductionmentioning
confidence: 99%
“…The physicochemical properties of nanomaterials, and their applications in medicine, biology and biotechnology, have also been reviewed in several papers (see, e.g. Ansari & Husain, 2012;Dufort et al 2012;Khlebtsov & Dykman, 2010;Mahmoudi et al 2011;Mahon et al 2012;Mandal et al 2014;Salata, 2004;Saptarshi et al 2013;Shemetov et al 2012). Various aspects of the computational methods employed in modeling and simulation of protein-surface interactions are addressed in other reviews, including issues in computational modeling of peptide-surface interactions (Di Felice & Corni, 2011), problems with these simulation techniques and approaches to multiscale modeling of soft matter that are transferable to proteinsurface systems (Praprotnik et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to this, peptides are very useful components in creating self‐assembled nanostructures because of their biocompatibility, biodegradability and biofunctionality 10.…”
Section: Peptide and Lipopeptide Self‐assemblymentioning
confidence: 99%